The open mind: essays in honour of Christopher Rowland - Rowland, Christopher; Knight, Jonathan (Library of New Testament studies, 2015)
Chapter 5 -- THE OPEN HELL: A STUDY OF THE APOCALYPSE OF PETER -- Paul FosterChapter 6 -- THE DESCENDING SON OF MAN IN THE GOSPEL OF JOHN: A POLEMIC AGAINST MYSTICAL ASCENT TO SEE GOD -- Charles A. Gieschen; Chapter 7 -- HEAVENLY MYSTERIES AND EARTHLY RICHES: AN APOCALYPTIC PERSPECTIVE ON THE PROPER USE OF WEALTH IN THE GOSPEL ACCORDING TO LUKE? -- Andrew Gregory; Chapter 8 -- THE CHRISTOLOGY OF THE ASCENSION OF ISAIAH: DOCETIC OR POLYMORPHIC? -- Jonathan Knight.